PENGARUH VIRAL MARKETING, CELEBRITY ENDORSER DAN BRAND AWARENESS TERHADAP KEPUTUSAN PEMBELIAN ESTEH INDONESIA PADA GENERASI Z - Intania (2022)
This research is a quantitative study that aims to determine whether there is an influence between viral marketing, celebrity endorser and brand awareness variables on the purchasing decision of Esteh Indonesia in generation z who live in Bogor. The study used 100 respondents, with a purposive sampling technique. The analysis technique used is the path analysis method and data processing is done through SmartPLS 4.0. The results of the test obtained (1) viral marketing has a significant effect on purchasing decisions for Esteh Indonesia in generation z in Bogor. (2) the celebrity endorser has no significant effect on the purchasing decision of Esteh Indonesia in generation z in Bogor. (3) brand awareness has a significant effect on purchasing decisions for Esteh Indonesia in generation Z in Bogor.